Activities of Daily Living Limitations in Middle-aged and Older Adults with Joint Disorders and Osteoporosis: Indonesia Longitudinal Aging Survey 2023 - Aryani, Desfalina; M. Irzal, Mufti As Siddiq As Siddiq; Sianipar, Agustina (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Population ageing is associated with an increasing prevalence of limitations in activities of daily living. Joint disorders and osteoporosis are common health problems among older adults and may begin to emerge during middle age, potentially accelerating functional decline. However, studies examining the association between these conditions and limitations in activities of daily living in Indonesia remain limited. This study aimed to analyse the association between joint disorders and osteoporosis and limitations in activities of daily living among middle-aged and older adults in Indonesia. This study employed a cross-sectional design using data from the Indonesia Longitudinal Aging Survey (ILAS) 2023. The sample consisted of 4,084 respondents aged ≥45 years from nine provinces in Indonesia. Limitations in activities of daily living were assessed using the Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) instruments, whereas the main independent variables, joint disorders and osteoporosis, were identified through doctor-confirmed self-reported diagnoses. Data were analysed using logistic regression models. The prevalence of ADL limitations was 9.4%, while IADL limitations were reported in 65.4% of respondents. After adjusting for sociodemographic factors, joint disorders (adjusted odds ratio [aOR] = 1.91; 95% CI: 1.46-2.51) and osteoporosis (aOR = 4.11; 95% CI: 2.41-7.01) remained associated with ADL limitations. However, both conditions were no longer associated with IADL limitations. Lower educational attainment and unemployment status were associated with IADL limitations.Joint disorders and osteoporosis are associated with limitations in basic functioning (ADL), whereas limitations in instrumental functioning (IADL) are more influenced by sociodemographic factors. Disability prevention strategies should integrate clinical management and social interventions to maintain independence among older adults. Keywords: Older Adults, Joint Disorders, Osteoporosis, Activities Of Daily Living, Instrumental Activities Of Daily Living